The spiritual and mental health assessment of social workers working for Internally Displaced Persons during Covid-19 in Myanmar - Saw Ye Win Thu; Hsiu-Ching Chen (Qanun Medika: Jurnal Kedokteran Fakultas Kedokteran Universitas Muhammadiyah Surabaya, 2023)
This study applies the spiritual assessment viewpoint toanalyze the responses of participants who are working for InternallyDisplaced Persons (IDPs) in Kachin and Northern Shan State,Myanmar. It was an online survey of workers' work experience in April2022. The analysis applies a quantitative research method to explorethe spirituality of social workers who are working in conflict-affectedareas where works are stressful, and the guarantee of security isuncertain. To analyze participants’ spirituality, in quantitative method,the form of the Spirituality Assessment of Worker Working for IDPs(SASSIDPs) is designed as three dimensions of SASSIDPs: Healthyself-awareness (HSA), healthy relationship (HR), and healthy feeling(HF). The results are conducted with the Social Science StatisticsSoftware (SPSS) 22.0 for the statistical analysis. Most of theparticipants are female (66%) and 34% are male. The results of in threedimensions of the SASSIDPs are different from their socialcharacteristics: in gender, males and females are significantly differentin HF of SASSIDPs (t=-3.21**), female is higher than male; in termsof religion/faith, group of “Christianity” is significantly different fromthe group of “non-Christian” in HF(t=-2.833**), and “non-Christianity”group gets higher agree than “Christianity” group; in term of workingyears, people who have been working below 2 years has significantlydifferent from 3 years above in HSA (t=2.918**); in term of age, thereis no difference among the different age groups.